Omalus biaccinctus - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
4. Omalus biaccinctus (Buysson, 1892) Ellampus biaccinctus Buysson in André 1892: 152. Syntypes ♂, ♀; France (MNHN) (examined). Omalus biaccinctus : Linsenmaier 1959: 18, Valkeila 1962: 63, Erlandsson 1971: 88, Banaszak 1980: 10, Silfverberg 1981: 61, Vikberg 1986b: 67, Cederberg 2000: 177, Söderman & Vikberg 2003: 44, Soon 2004: 19, 45, Cederberg 2005: 290, Sörensson 2008f, Allearter.dk 2010, Orlovskytė et al. 2010: 153, Paukkunen 2010: 542, Rosa & Soon 2012, Dyntaxa 2013. Material examined. Denmark: LFM : Kaerstrup, 1913, 1 ♀; Søholt, 1917, 1 ♀; * Latvia: Dalbe, 22.VI.1973, 1 ♀ (V. Tumšs); Langstini, 25.VII.1971, 1 ♀ (V. Tumšs); Upseims, 16.VII.1974, 1 ♀ (V. Tumšs); * Norway: BØ : Hole, Utstranda, 25.VI–2.VIII.2011, 2 exx. (F. Ødegaard); Ø : Hvaler, Asmaløy, 25.VI.2010, 1 ex. (F. Ødegaard); *Russian Fennoscandia: Ik : Metsäpirtti [= Zaporozhskoe], 12.VII.1934, 1 ♀ (A. Merisuo). Distribution. Denmark, Estonia, Finland, * Latvia, * Norway, Sweden, *Russian Fennoscandia.—Westpalearctic: from West Europe to West Asia (Linsenmaier 1959). Most common in the Mediterranean area (Mingo 1994). Remarks. Omalus biaccinctus is a rare species in the Nordic and Baltic countries. It has not yet been recorded in Lithuania. The species has been classified as vulnerable in Finland (Paukkunen 2010). In Sweden it is also uncommon, but was excluded from the latest national red list (Cederberg et al. 2010). The Latvian specimens were found in LMSZ in Riga, where they had been erroneously identified as O. aeneus by Tumšs. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on pages 9-10, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Brucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32, 1 - 232.", "Valkeila, E. (1962) Eraiden lounaissuomalaisten luonnonhistoriallisten maakuntien (V, U, St ja EH) myrkkypistiaiset (Hymenoptera, Aculeata). Lounais-Hameen Luonto, 13, 63 - 73.", "Erlandsson, S. (1971) Catalogus Insectorum Sueciae XIX. Hymenoptera: Aculeata. Entomologisk Tidskrift, 22, 87 - 94.", "Banaszak, J. (1980) Zlotolitki Chrysididae. Katalog Fauny Polski, 26, 1 - 52.", "Silfverberg, H. (1981) Additions to the Finnish insect fauna during the years 1976 - 1980. Notulae Entomolgicae, 61, 45 - 61.", "Vikberg, V. (1986 b) A checklist of aculeate Hymenoptera of Finland (Hymenoptera, Apocrita Aculeata). Notulae Entomologicae, 66, 65 - 85.", "Cederberg, B. (2000) Steklar - Sawflies, Wasps, Ants & Bees, Hymenoptera. In: Gardenfors, U. (Ed.), Rodlistade arter i Sverige 2000 - The 2000 Red List of Swedish Species. ArtDatabanken, SLU, Uppsala, pp. 171 - 184.", "Soderman, G. & Vikberg, V. (2003 [\" 2002 \"]) Suomen myrkkypistiaisten luettelo ja levinneisyys. Sahlbergia, 7, 41 - 66.", "Soon, V. (2004) Eesti kuldherilased (Hymenoptera, Apocrita, Chrysididae). Master's thesis, University of Tartu. 81 pp. Available from: http: // dspace. utlib. ee / dspace / bitstream / handle / 10062 / 1236 / Soon. pdf; jsessionid = 6617 B 92 C 3 E 468623 BC 1 5 CAC 1 E 8 B 95 C 67? sequence = 5 (accessed 1 November 2013)", "Cederberg, B. (2005) Steklar - Wasps, Hymenoptera. In: Gardenfors, U. (Ed.), Rodlistade arter i Sverige 2005 - The 2005 Red List of Swedish Species. ArtDatabanken, SLU, Uppsala, pp. 283 - 297.", "Sorensson, M. (2008 f) Omalus biaccinctus, mork glansguldstekel. - Artfaktablad. Available from http: // www. artfakta. se / artfaktablad / Omalus _ Biaccinctus _ 102638. pdf (accessed 1 November 2013)", "Orlovskyte, S., Budriene, A. & Budrys, E. (2010) Check-list of cuckoo-wasps (Hymenoptera: Chrysididae) of Lithuania. New and rare for Lithuania insect species, 22, 141 - 156.", "Paukkunen, J. (2010) Stinging wasps. In: Rassi, P., Hyvarinen, E., Juslen, A. & Mannerkoski, I. (Eds.), The 2010 Red List of Finnish Species. Finnish Ministry of Environment & Finnish Environment Institute, Helsinki, pp. 529 - 544.", "Rosa, P. & Soon, V. (2012) Fauna Europaea: Chrysididae. In: Mitroiu, M. - D. (Ed.), Fauna Europaea: Hymenoptera, version 2. 5. Available from http: // www. faunaeur. org (accessed 1 November 2013)", "Dyntaxa (2013) Svensk Taxonomisk Databas - Swedish Taxonomic Database (version 1.1.5059.20729). Available from: http: / / www. dyntaxa. se / (accessed 1 November 2013)", "Cederberg, B., Abenius, J., Hellqvist, S., Hogmo, O., Larsson, M. & Sorensson, M. (2010) Steklar - Wasps, Hymenoptera. In: Gardenfors, U. (Ed.), Rodlistade arter i Sverige 2010 - The 2010 Red List of Swedish Species. ArtDatabanken, SLU, Uppsala, pp. 345 - 360."]}